First you must bring 6 to the other side of the equation so it equals zero. To do this subtract 6 to both sides
20p^2+33p+16 - 6=6 - 6
20p^2+33p+10=0
Use the quadratic equation to solve this (image of the quadratic equation is below)
Remember that quadratic functions are set up like so:
That means that in this equation...
a = 20
b = 33
c = 10
^^^Plug these numbers into the quadratic equation and solve...
Keep in mind that +/- is ±
---> -2/5 ---> -0.4
---> -5/4 ---> - 1.25
Hope this helped!
~Just a girl in love with Shawn Mendes